Is the socioeconomic inequality in stroke prognosis changing over time and does quality of care play a role?. (March 2023) - Hyldgård, Vibe Bolvig; Søgaard, Rikke; Valentin, Jan Brink; Lange, Theis; Damgaard, Dorte; Johnsen, Søren Paaske
Introduction: In a publicly financed healthcare system we aimed to study the development in socioeconomic disparity in ischemic stroke outcomes over time. In addition, we study whether the healthcare system affects these outcomes through the quality of early stroke care when adjustments are made for various patient characteristics incl. comorbidity and stroke severity. Patients and methods: Using nationwide, detailed individual-level register-data we analysed how income-related and education-related inequality in 30-day mortality and 30-day readmission risk developed between 2003 and 2018. In addition, focusing on income-related inequality, we applied mediation analyses to estimate the mediating role of quality of acute stroke care on 30-day mortality and 30-day readmission. Results: A total of 97, 779 individual ischemic stroke patients were registered in Denmark with a first ever stroke in the study period. Three-point-seven percent died within 30 days of their index-admission and 11.5% were readmitted within 30 days of discharge. The income-related inequality in mortality remained virtually unchanged over time from an RR of 0.53 (95% CI: 0.38; 0.74) in 2003–06 to RR 0.69 (95% CI: 0.53; 0.89)) in 2015–18 when high income was compared to low income (Family income-time interaction: RR 1.00 (95% CI: 0.98–1.03)). A similar but less uniform trend was found for the education-related inequality in mortality (Education-time interaction: RR 1.00 (95% CI: 0.97–1.04)). The income-related disparity in 30-day readmission was smaller than in 30-day mortality and it diminished over time from 0.70 (95% CI: 0.58; 0.83) to 0.97 (95% CI: 0.87; 1.10). The mediation analysis showed no systematic mediating effect of quality of care on neither mortality nor readmission. However, it cannot be ruled out that residual confounding may have washed out some mediating effects. Discussion and Conclusion: The socioeconomic inequality in stroke mortality and re-admission risk has yet to be eliminated. Additional studies from different settings are warranted in order to clarify the impact of socioeconomic inequality of quality of acute stroke care.